O sistema de vigilância alimentar e nutricional como ferramenta de gestão na atenção básica - Botega, Ariane de Oliveira (2018)
The Food and Nutrition Surveillance System (SISVAN) consists of a health information tool that provides management of food and nutritional care, epidemiological diagnosis of the nutritional situation, temporal trends and determining factors, formulation of public policies, establishment of programs intervention and promotion health and nutrition, qualifying health care in basic attention of the SUS. The implementation of food and nutritional surveillance through SISVAN is essential, especially for infants because nutritional status exerts a decisive influence on the risks of morbidity and mortality, child growth and development. The objective of this study was to analyze SISVAN as a health management tool in the basic attention of the 32 cities within a health region in the south of the country, as well as to describe and characterize the nutritional status of infants followed by SISVAN Web and to compare nutritional monitoring coverage of these children registered in the Module Manager Report SISVAN Web and SISVAN Management Module of “Bolsa Familia”. This is an ecological observational study. Data on the nutritional profile of infants were investigated on the basis of the Department of Informatics of the SUS, Manager Module of SISVAN - Annual consolidated reports of the nutritional status of children under two years, the period from 2008 to 2015, and at the Brazilian Institute of Geography and Statistics. To analyze the nutritional profile, the anthropometric parameters established by the SISVAN Manual were used. There was under-registration (25% of cities) and a limited percentage of nutritional follow-up of children under two years of age at SISVAN Web (2.59%), indicating a nutritional profile of eutrophy for the majority (87.50%) of the cities that accompanied the children in this system. In addition, there was prioritization of monitoring of nutritional status in the SISVAN Management Module of the “Bolsa Família”, possibly because this module is linked to the receipt of public funds. The results found corroborate with other studies and national health surveys, indicating a limited understanding and appropriation by health professionals of SISVAN as a tool health management, which impacts on the legitimation of the planning of actions and, consequently, the identification and anticipation of health problems in the population. It is inferred that the systematic and expanded use of SISVAN is a challenge to be achieved. It is suggested that permanent education be promoted for professionals who work in the basic attention of the cities within the operationalization and integration of health information systems, so that the information produced can be used as a strategic planning element in daily practices and health care.